2019
DOI: 10.5137/1019-5149.jtn.27977-19.2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery versus minimal puncture drainage surgery for treatment of supratentorial intracerebral hemorrhage

Abstract: AIM:To compare neuroendoscopy versus minimal puncture drainage for surgical treatment of supratentorial hypertensive intracerebral hemorrhage.MATERIAL and METHODS: A total of 108 cases involving supratentorial intracerebral hemorrhage were retrospectively analyzed. In 30 cases, endoscopic surgery was performed, while 78 cases involved puncture surgery. We compared hematoma clearance rate, postoperative rebleeding rate, incidence of postoperative complications, operation duration, and Glasgow coma score seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Previous studies of endoscopic hematoma removal have reported a hematoma removal rate of 90.3% (87.0%-90.9%) and a rebleeding rate of 3.3% (2.9%-4.0%). 7 , 11 , 12 , 26 - 32 ) The surgical results in this study were comparable to those previously reported, and the hematoma stiffness was correlated with these results. As expected, group S had more FHR and shorter endoscopic procedure times than group F. Furthermore, both patients whose endoscopic hematoma removal procedure was abandoned belong to group F. Therefore, hematoma stiffness correlates with the surgical results, and predicting hematoma stiffness during endoscopic surgery may help surgeons determine the appropriate treatment strategies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies of endoscopic hematoma removal have reported a hematoma removal rate of 90.3% (87.0%-90.9%) and a rebleeding rate of 3.3% (2.9%-4.0%). 7 , 11 , 12 , 26 - 32 ) The surgical results in this study were comparable to those previously reported, and the hematoma stiffness was correlated with these results. As expected, group S had more FHR and shorter endoscopic procedure times than group F. Furthermore, both patients whose endoscopic hematoma removal procedure was abandoned belong to group F. Therefore, hematoma stiffness correlates with the surgical results, and predicting hematoma stiffness during endoscopic surgery may help surgeons determine the appropriate treatment strategies.…”
Section: Discussionsupporting
confidence: 91%
“…While it remains unclear which MIS procedure is the best, several studies comparing various surgical methods suggested that endoscopic surgery achieved a higher hematoma removal rate and better functional outcomes than stereotactic surgery. [10][11][12][13] In endoscopic surgery, the hematoma is often removed successfully; however, removal may be challenging in some cases. When removing brain tumors, especially meningiomas, tumor consistency is considered an important factor affecting the surgical outcome.…”
Section: Introductionunclassified
“…A recent meta-analysis[ 8 ] has reported that endoscopic evacuation is more favorable than catheter drainage. However, other researchers claim that the latter is more favorable[ 4 , 9 ]. Moreover, with the help of more accurate instruments and neuronavigation methods, endoscopic hematoma evacuation can be conducted under the guidance of visualization of ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of modern imaging technology, neuronavigation technology has been commonly used in surgery [ 4 – 7 ]. Neuroendoscopic intracerebral hematoma removal versus hematoma cavity puncture and drainage is a minimally invasive surgical option for HICH [ 8 , 9 ]. Herein we discuss the respective advantages of these two techniques with the aid of neuronavigation.…”
Section: Introductionmentioning
confidence: 99%